2016
DOI: 10.4103/0019-5278.203140
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of blood-borne infections and burden of occupational exposures to blood and body fluids among health care personnel in a tertiary care teaching hospital

Abstract: Background and Objectives:Occupational exposures (OEs) to blood and body fluids (BBFs) pose significant risk of transmission of blood-borne infections (BBIs) to health care personnel (HCP) and are grossly underreported. We aimed to study the awareness of BBIs and their prevention, burden of OEs, assess factors contributing to them and their poor reporting and assess the practices for their prevention among HCP.Materials and Methods:This cross-sectional study conducted at a tertiary care teaching hospital locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This finding may allow hospitalised patients to experience less pain and discomfort with less risk of bleeding issues from blood drawing via venipuncture. This benefit was consistently discussed in a previous study (Swetharani et al, 2016 In addition, using devices such as saline locks for frequent blood sampling would be also recommendable for healthcare providers. It would decrease working time and load for nurses or technicians to draw blood from their patients.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This finding may allow hospitalised patients to experience less pain and discomfort with less risk of bleeding issues from blood drawing via venipuncture. This benefit was consistently discussed in a previous study (Swetharani et al, 2016 In addition, using devices such as saline locks for frequent blood sampling would be also recommendable for healthcare providers. It would decrease working time and load for nurses or technicians to draw blood from their patients.…”
Section: Discussionmentioning
confidence: 80%
“…Bedside blood sampling is commonly performed by nurses in most institutions. Therefore, the higher the frequency of the blood tests, the greater the burden for the nurse as well as the occurrence of discomfort for the patient (Swetharani, Vinod, Hamide, Dutta, & Harichandrakumar, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently conducted studies in Bosnia and Herzegovina (19) , Serbia (26) and China (27) show that many studies that investigated incidents of blood exposures showed some significant differences in prevalence between different professional groups. As an example a study in China in the period from 2015-2018 year proved that nurses are in greater risk of exposure of blood-transfer infections (28) , while other studies in Serbia, India and Jamaica proved a greater risk of exposure among physicians (26,29,30) . Also, the profile of the nurses/ technicians did not prove to be a predictor for the occurrence of professional exposure to blood and body fluids transmissible infections.…”
Section: Discussionmentioning
confidence: 99%